Phases, metrics, and techniques of product discovery - Gonçalo Canhoto; Rafael Almeida; Miguel Mira da Silva (Journal of Innovation and Entrepreneurship)
Abstract This paper aims to explore, synthesize, and analyze gray literature on the product discovery process, focusing on its key metrics, phases, and techniques to offer valuable insights into effective product management practices. A comprehensive review and analysis of gray literature sources, including online articles, blog posts, reports, and books, was undertaken to construct a thorough perspective on the product discovery process. The review categorizes the main themes of product discovery into phases, metrics, and techniques, providing a holistic summary of the methods and best practices for successful product discovery. The review is based on gray literature, which lacks the academic rigor of peer-reviewed sources despite providing valuable industry insights. Hence, it is recommended that future research incorporate more peer-reviewed academic literature to supplement these findings for a more comprehensive understanding of the product discovery process. This review synthesizes the existing gray literature on product discovery, offering an informative overview of the field's current practices, methods, and strategies. It highlights key insights that could help organizations and practitioners better understand the product discovery landscape, potentially informing the enhancement of their product development practices to align with market opportunities and user needs. Improved understanding and application of product discovery could lead to more user-centric products, positively impacting user satisfaction and engagement. Additionally, it could influence the competitiveness and success of product companies in the market, influencing employment and economic growth. This review synthesizes the existing gray literature on product discovery, offering an informative overview of the field's current practices, methods, and strategies. It highlights key insights that could help organizations and practitioners better understand the product discovery landscape. Thus, it serves as a unique, timely resource for companies across industries, aiming to understand better and potentially optimize their product management strategies.